Forest biotechnology: an extension of tree improvement. (29th June 2007) - Kellison, Robert C.; Balocchi, Claudio E.; Valenzuela, Sofia; Rodriguez, Jaime
Forest genetics as a science has existed since the 1940s. With the depiction of the structure of DNA in 1953 by Watson and Crick, some forest geneticists were inspired to apply this knowledge to trees. Since that time the science of molecular biology has evolved considerably. This paper summarises the applications of biotechnology to trees, the traits and trials for genetically engineered trees, possible applications to trees, environmental and social benefit and biosafety.